Evaluating the potential of additive manufacturing in repair for remanufacturing using AHP method: case study of automotive brake caliper - Iva Song Ci Way; Nurhasyimah Abd Aziz; Nurfadzylah Awang; Dzuraidah Abd Wahab (Penerbit Universiti Kebangsaan Malaysia, 2023)
In line with technological advancements in the era of IR 4.0, it is crucial for remanufacturing process to shift towards the more sustainable automated process. One of the remanufacturing activities that is currently gaining significant interest is an additive repair process. The repair processes in remanufacturing are usually conducted conventionally which caused inherent defects on the used part due to the heat generation and residual stress exerted during the process. Therefore, additive repair processes through the metal additive manufacturing should be considered in remanufacturing which offers substantial benefits in terms of efficiency and environmental effects. However, the inclusion of additive repair is still at the infancy stage where thorough investigation is necessary to overcome the issues in the process. The raised issues include the printability, bonding behaviour between two metals and quality of the repaired part. It is important to ascertain the compatibility of the additive repair process with the certain type of defects. This study focuses on the evaluation of defects or failure in an automotive brake caliper component using the Analytic Hierarchy Process (AHP) decision-making method. The main objective is to consider both qualitative and quantitative aspects for selecting the suitable repair process by reflecting the potential defects as the criteria and sub-criteria. Three respondents were participated to provide the priority scores through paired comparisons for each criterion, sub-criterion, and alternative involved. The study found that the Directed Energy Deposition (DED) process is the primary choice of respondents with the potential to be considered as a repair process for additive manufacturing with the score of 0.65. Overall, an AHP method is able to evaluate subjective opinions to select the suitable repair process in remanufacturing application.